Persuasive Communication in Cultivating Prayer Worship: A Case Study of Mrs. Tiahiroh's Family - Samir Humaidi; Dika Sahputra (Jurnal Ilmiah Syi'ar, 2024)
This study seeks to evaluate maternal persuasive communication with children aged 5-10 years about the instillation of prayer, focusing on the Buk Tiahiroh family as a case study. This research employed a descriptive qualitative methodology for data gathering, utilizing observation, interviews, and documentation. The informant in this study was Mrs. Tiahiroh, the biological mother of her children. Data analysis strategies employ data reduction, data display, and conclusion formulation. This research employs a triangulation method for data validity testing. The findings of this research indicate that Mrs. Tiahiroh employs persuasive communication with her child, namely a two-component approach that integrates attention and comprehension into a singular acceptance factor. The mother's communication with her child is highly effective within the family, as it addresses various crucial areas, including phases of attention, comprehension, memory, and action. These factors render communication between moms and children inside the family successful and significant.